2008
DOI: 10.1556/oh.2008.28387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oligofructose containing diet in obese persons

Abstract: The results of this pilot study appear to demonstrate that the Jerusalem artichoke concentrate produced by a new technology can be a promising component of future diet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Similarly, a recent parallel study reported supplementation of volunteers ( n 51) with 14 g Jerusalem Artichoke concentrate (containing OF) daily for 12 weeks reduced rated hunger ( 59 ) . However, it was unclear whether effects on hunger were significant.…”
Section: The Role Of Scfa In Appetite Regulationmentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, a recent parallel study reported supplementation of volunteers ( n 51) with 14 g Jerusalem Artichoke concentrate (containing OF) daily for 12 weeks reduced rated hunger ( 59 ) . However, it was unclear whether effects on hunger were significant.…”
Section: The Role Of Scfa In Appetite Regulationmentioning
confidence: 86%
“…Less compelling is anthropometric and food intake data from chronic intervention studies, although these were not the main outcomes of interest for all studies (65)(66)(67)(68)(69)(70)(71)(72) except for two (59,60) . One study reported daily supplementation with 14 g Jerusalem Artichoke concentrate (containing OF) for 12 weeks significantly reduced BMI and % body fat levels (59) , while another reported daily supplementation with 21 g OF significantly reduced BW, fat mass and central fat mass (60) . However, none of the other studies found a significant influence of inulin-type fructan supplementation on BW post-intervention (59,65,66,(68)(69)(70)(71)(72) or on food intake during the intervention (65)(66)(67)(68) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation with OFS is associated with a reduction in body fat in rodents and in adults and children with overweight or obesity ( 12 , 16 , 21 , 40 ). As hypothesized, the actions of OFS and sitagliptin resulted in greater weight loss than either treatment alone in obese female rats in the prepregnancy period.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, due to its biosynthetic capacity, high yields and low agronomic requirements, chicory has high potential to become a versatile production host for molecular farming by providing many additional health-related products (Meijer and Mathijssen 1992). These include immunomodulatory prebiotics (Roberfroid 2008) and pharmaceuticals to prevent lifestyle diseases [e.g., obesity (Antal et al, 2008)], to promote gut health, to stimulate the immune system (Bodera 2008) or as alternative antibiotics (Sinkovic et al, 2017;Peña-Espinoza et al, 2018). To achieve this, new chicory variants need to be developed.…”
Section: Introductionmentioning
confidence: 99%